O Léxico do canto do Mangue - Santos, Wellington Lopes dos (2010)
Is at the lexicon that if reflects the diverseness as of visions as of world of the guys AND their varied norms crop. In the case of one language well into private like the from a community fishing boat is there a level vocabulary integrates - region, inherent to the ambit social restrained where it is used. The terminology integrates - region bond - in case that within doors of that community because of several suit, within doors they: The knowledge as of world AND the techniques specific for the execution from the fish. About to so much, this research does have as a objective central investigate at the light of the theories linguistics (Lexicology, Lexicography, Semantics, Sociolinguistics, Etnolinguistics and Dialetology) the terminology than it is to prevaiu at the community as of anglers from the I sing from the hose well into Natal/RN via the layout by one glossary than it is to he describes, most of all, the terms attendees he might give universe vocabulary well into Portuguese language.